Relationship between body dissatisfaction, insufficient physical activity, and disordered eating behaviors among university students in southern China - Ming Hao; Yifei Fang; Wenjing Yan; Junwang Gu; Yanbin Hao; Chunmei Wu (BMC Public Health, 2022)
Abstract Background With an increasing incidence of obesity, the relationship between obesity and body image has become a hot research topic worldwide. From high school to university, young people experience changes in their social environment. University students have a high incidence of eating disorders and insufficient physical activity. The purpose of this study was to explore the relationship between body dissatisfaction, insufficient physical activity, and disordered eating behaviors among university students in southern China. Methods In total, 1296 university students aged 18–23 years were recruited for this study. The participants completed anthropometric measurements, the Physical Activity Rating scale-3 (PARS-3), and the Chinese-Dutch Eating Behavior Questionnaire (C-DEBQ). The ideal weight and silhouette were reported by university students using a questionnaire. Results Compared with men, young women had a higher level of body dissatisfaction. For men, body mass index (BMI; β = 0.76, P <  0.01), physical activity score (β = − 0.11, P <  0.01), and restrained eating score (β = 0.10, P <  0.01) were the significant factors predictive of body dissatisfaction. For women, BMI (β = 0.57, P <  0.01), muscle mass (β = 0.12, P <  0.01), physical activity score (β = − 0.11, P <  0.01), and restrained eating score (β = 0.09, P <  0.01) were the significant factors predictive of body dissatisfaction. Conclusions University students with high body dissatisfaction had lower physical activity scores and higher restrained eating scores. The data presented here highlight the impact of university students’ body dissatisfaction on physical activity deficiency and disordered eating behaviors in China.